Représenter volailles et volaillères dans la peinture italienne du Cinquecento - Valérie Boudier (Revue d'ethnoécologie, 2017)
Painted works are not easy to decipher and scenes of poultry sale by North Italian artists Vincenzo Campi and Bartolomeo Passerotti are not snapshots of every day popular life of the Sixteenth Century, in Italy. Artistic image has a language of its own the Art historians attempt to decipher by analyzing the objectives, conventions, styles, and techniques of each work. This plastic analysis must be crossed with the study of literary, artistic and culinary texts of those times, and this in order for the analysis to encompass a social and cultural background. It's this crossing in the analysis that allows us to suggest that the topic of the poultry and poultries's seller have place and pictorial treatment quite original in paintings. They seem to embody the modalities of the viewer's gaze in the pictorial organization of genre scenes by these two North Italian artists of the Sixteenth Century.